Rural ambulatory care pharmacists providing in-clinic and home visit services improve adherence to long-acting injectable antipsychotics - Heng "Helen" Chang, PharmD, BCPS; Laura Michelle Vaughn, PharmD, BCACP, BC-ADM, CDCES; Danica Liu, PharmD (American Association of Psychiatric Pharmacists, 2024)
Patients with schizophrenia often experience symptoms such as poor insight and disorganized thought, which limit their ability to seek and receive care consistently. In rural settings, systemic factors, including limited resources and transportation, further contribute to difficulties in health care access. Long-acting injectable antipsychotics (LAIs) can improve medication adherence and reduce hospitalizations from relapse. Opportunities exist for pharmacists to provide individualized care and improved health care access. The pilot service took place in ambulatory care clinics and home care settings. Pharmacists performed weekly reviews of patients with active orders for LAIs, coordinated care with nonadherent patients, and offered follow-up appointments in the Patient Centered Medical Home (PCMH). For patients unable to be reached, outreach pharmacists provided psychiatric assessment and LAI medication administration at home visits. There were 10 patients with LAI prescriptions in the past year selected for review. The period reviewed was 90 days before and after start of service. Pharmacist interventions resulted in 4 patients reestablished with care who were previously lost to follow-up. The percentage of days covered by LAI fills increased from an average 26% to 67% of days covered (P = .06). Total emergency room visits related to mental health episodes decreased from 11 to 2 visits (P = .03). Four patients who did not have metabolic lab monitoring in more than 1 year received lab monitoring as indicated. PCMH pharmacy services, including home visits by outreach pharmacists, may improve access and bridge care gaps for patients on LAIs by providing community-based services in addition to traditional clinic-based care.